Clinical Signs of Impending Death in Cancer Patients. (23rd April 2014) - Hui, David; dos Santos, Renata; Chisholm, Gary; Bansal, Swati; Silva, Thiago Buosi; Kilgore, Kelly; Crovador, Camila Souza; Yu, Xiaoying; Swartz, Michael D.; Perez-Cruz, Pedro Emilio; Leite, Raphael de Almeida; Nascimento, Maria Salete de Angelis; et al.
Abstract: Background: The physical signs of impending death have not been well characterized in cancer patients. A better understanding of these signs may improve the ability of clinicians to diagnose impending death. We examined the frequency and onset of 10 bedside physical signs and their diagnostic performance for impending death. Methods: We systematically documented 10 physical signs every 12 hours from admission to death or discharge in 357 consecutive patients with advanced cancer admitted to two acute palliative care units. We examined the frequency and median onset of each sign from death backward and calculated their likelihood ratios (LRs) associated with death within 3 days. Results: In total, 203 of 357 patients (52 of 151 in the U.S., 151 of 206 in Brazil) died. Decreased level of consciousness, Palliative Performance Scale ≤20%, and dysphagia of liquids appeared at high frequency and >3 days before death and had low specificity (<90%) and positive LR (<5) for impending death. In contrast, apnea periods, Cheyne-Stokes breathing, death rattle, peripheral cyanosis, pulselessness of radial artery, respiration with mandibular movement, and decreased urine output occurred mostly in the last 3 days of life and at lower frequency. Five of these signs had high specificity (>95%) and positive LRs for death within 3 days, including pulselessness of radial artery (positive LR: 15.6; 95% confidence interval [CI]: 13.7–17.4), respiration with mandibular movement (positive LR: 10; 95% CI: 9.1–10.9), decreased urine output (positive LR: 15.2; 95% CI: 13.4–17.1), Cheyne-Stokes breathing (positive LR: 12.4; 95% CI: 10.8–13.9), and death rattle (positive LR: 9; 95% CI: 8.1–9.8). Conclusion: We identified highly specific physical signs associated with death within 3 days among cancer patients. Abstract : The authors examined the frequency and onset of 10 bedside physical signs and their diagnostic performance for impending death. They identified highly specific physical signs associated with death within 3 days among cancer patients.